Effects of whole body vibration training on muscle strength and sprint performance in sprint-trained athletes - Delecluse, C.; Roelants, M.; Diels, R.; Koninckx, E.; Verschueren, S. (International Journal of Sports Medicine, 2005)
Despite the expanding use of Whole Body Vibration training among athletes, it is not known whether adding Whole Body Vibration training to the conventional training of sprint-trained athletes will improve speed-strength performance. Twenty experienced sprint-trained athletes (13 ?, 7 ?, 17 - 30 years old) were randomly assigned to a Whole Body Vibration group (n = 10: 6 ? and 4 ?) or a Control group (n = 10: 7 ?, 3 ?). During a 5-week experimental period all subjects continued their conventional training program, but the subjects of the Whole Body Vibration group additionally performed three times weekly a Whole Body Vibration training prior to their conventional training program. The Whole Body Vibration program consisted of unloaded static and dynamic leg exercises on a vibration platform (35 - 40 Hz, 1.7 - 2.5 mm, Power Plate®). Pre and post isometric and dynamic (100°/s) knee-extensor and -flexor strength and knee-extension velocity at fixed resistances were measured by means of a motor-driven dynamometer (Rev 9000, Technogym®). Vertical jump performance was measured by means of a contact mat. Force-time characteristics of the start action were assessed using a load cell mounted on each starting block. Sprint running velocity was recorded by means of a laser system. Isometric and dynamic knee-extensor and knee-flexor strength were unaffected (p > 0.05) in the Whole Body Vibration group and the Control group. As well, knee-extension velocity remained unchanged (p > 0.05). The duration of the start action, the resulting start velocity, start acceleration, and sprint running velocity did not change (> 0.05) in either group. In conclusion, this specific Whole Body Vibration protocol of 5 weeks had no surplus value upon the conventional training program to improve speed-strength performance in sprint-trained athletes.